Epigenetic suppression of the antitumor cytotoxicity of NK cells by histone deacetylase inhibitor valproic acid - Shi, Xiumin (Am J Cancer Res, 2016)
Natural killer (NK) cells play an essential role in the fight against tumor development. The therapeutic use of autologous NK cells has been exploited to treat human malignancies, yet only limited antitumor activity is observed in cancer patients. In this study, we sought to augment the antitumor activity of NK cells using epigenetic approaches. Four small molecules that have been known to promote epigenetic reprogramming were tested for their ability to enhance the activity of NK cells. Using a tumor cell lysis assay, we found that the DNA demethylating agent 5-azacytidine and vitamin C did not significantly affect the tumor killing ability of NK cells. The thyroid hormone triiodothyronine (T3) slightly increased the activity of NK cells. The histone deacetylase inhibitor valproic acid (VPA), however, inhibited NK cell lytic activity against leukemic cells in a dose-dependent manner. Pretreatment using VPA reduced IFNγ secretion, impaired CD107a degranulation, and induced apoptosis by activating the PD-1/PD-L1 pathway. VPA downregulated the expression of the activating receptor NKG2D (natural-killer group 2, member D) by inducing histone K9 hypermethylation and DNA methylation in the gene promoter. Histone deacetylase inhibitors have been developed as anticancer agents for use as monotherapies or in combination with other anticancer therapies. Our data suggest that the activity of histone deacetylase inhibitors on NK cell activity should be considered in drug development.